Effects of photo biomodulation on peri-implantitis - Sahu, Natasha; Jalaluddin, Mohammad; Kar, Soubhagya Ranjan; Swain, Subham Kumar; Brahma, Priyanka; Nanda, Jagruti (International Journal of Research in Medical Sciences, 2022)
Periodontitis is a prevalent infectious disease in which the accumulation of bacterial plaque leads to an inflammatory reaction and destruction of supporting tissues around the teeth. The optimal goal in periodontal treatment is to eliminate the infection and to recreate the lost structures of cementum, periodontal ligament (PDL), and the alveolar bone with the reestablishment of their functions. Achieving this regenerative aim, however, remains a major challenge for periodontists. In order to increase the predictability and the efficacy of regenerative periodontal therapies, treatment modalities have moved from the conventional guided tissue treatments to novel tissue engineering and stem cell–based treatments. This is achieved either by transplantation of cells from outside sources to the periodontal defects or by enhancing the recruitment of endogenous host cells present in the area, known as cell homing methods. Photobiomodulation (PBM) therapy is a term used for exposure of cells/ tissues to low-level laser light or light-emitting diodes (LEDs), which is absorbed by specific photoreceptors in cells and may cause alteration at a molecular level inside cells without any heat generation leading to biological changes in cell metabolism and function.